Analysis and elimination on common‐mode interferences generated in the series‐resonant converter system of high‐power Tesla pulse driver. Issue 7 (1st September 2019) - Zhang, Yu; Su, Jiancang; Zheng, Lei; Li, Rui; Zhao, Liang; Yu, Binxiong; Cheng, Jie; Zeng, Bo; Xu, Xiudong
Abstract : Here, the distributed parametric circuit model of the series‐resonant charge power source in Tesla pulse driver is built. The generation mechanisms and characteristics of three types of d U /d t interferences and one kind of d i /d t interference are analysed. The voltage ringing and its corresponding d U /d t generated on the shared parts of the main circuit play as the input common‐mode interference (CMI) to the driving and triggering circuits. Circuit simulation and tests were both carried out to get the characteristics of high‐frequency CMIs in different key points of the main circuit. The generation and conducting of the high frequency CMIs were mainly caused by the abrupt charge and discharge resonances of the distributed capacitors. CMI suppression methods were put forward and demonstrated, such as resistor‐capacitor absorption between the middle points of the converter H‐bridge, resistor‐capacitor grounding at the negative port of the input DC mother line, the negative port grounding of the load capacitor, and symmetrical layout of two L‐C resonant arms in the series‐resonant circuit. The voltage ringing, d U /d t and d i /d t interferences in the series‐resonant converter were all effectively suppressed by these methods.